Olfactory Bulb Muscarinic Acetylcholine Type 1 Receptors Are Required for Acquisition of Olfactory Fear Learning - Ross, Jordan M.; Bendahmane, Mounir; Fletcher, Max L. (Frontiers in Behavioral Neuroscience, 2019)
The olfactory bulb (OB) receives significant cholinergic innervation and widely expresses cholinergic receptors. While acetylcholine (ACh) is essential for olfactory learning; the exact mechanisms by which ACh modulates olfactory learning, and whether it is specifically required in the OB remains unknown. Using behavioral pharmacology and optogenetics, we investigated the role of OB ACh in a simple olfactory fear learning paradigm. We find that antagonizing muscarinic acetylcholine receptors (mAChRs) in the OB during fear conditioning but not testing significantly reduces freezing to the conditioned odor, without altering olfactory abilities. Additionally, we demonstrate that m1 mAChRs, rather than m2, are required for acquisition of olfactory fear. Finally, using mice expressing channelrhodopsin in cholinergic neurons, we show that stimulating ACh release specifically in the OB during odor shock pairing can strengthen olfactory fear learning. Together these results define a role for ACh in olfactory associative learning and OB glomerular plasticity.